2019
DOI: 10.1177/1559325819891004
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Detection Technologies of Extracellular Vesicles and Application on Cancer Diagnostic

Abstract: The vast majority of cancers are treatable when diagnosed early. However, due to the elusive trace and the limitation of traditional biopsies, most cancers have already spread widely and are at advanced stages when they are first diagnosed, causing everincreasing mortality in the past decades. Hence, developing reliable methods for early detection and diagnosis of cancer is indispensable. Recently, extracellular vesicles (EVs), as circulating phospholipid vesicles secreted by cells, are found to play significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 171 publications
2
30
0
Order By: Relevance
“…Readily found in different body fluids, the number of circulating EVs is significantly higher in cancer patients, as reported in previous studies ( 7 , 29 , 30 ). Because of its transmission capacity in the tumor microenvironment or specific distant sites, these EVs have increasingly become recognized as key players in the cellular processes related to cancer pathogenesis, including tumorigenesis, angiogenesis, tumor invasion, progression, and metastasis ( Figure 1 ).…”
Section: Extracellular Vesicles’ Role In Cancer Development and Its Tsupporting
confidence: 85%
See 1 more Smart Citation
“…Readily found in different body fluids, the number of circulating EVs is significantly higher in cancer patients, as reported in previous studies ( 7 , 29 , 30 ). Because of its transmission capacity in the tumor microenvironment or specific distant sites, these EVs have increasingly become recognized as key players in the cellular processes related to cancer pathogenesis, including tumorigenesis, angiogenesis, tumor invasion, progression, and metastasis ( Figure 1 ).…”
Section: Extracellular Vesicles’ Role In Cancer Development and Its Tsupporting
confidence: 85%
“…MVs, with a diameter of 100–1,000 nm, are released by outward budding and fission of the plasma membrane. Growing evidence has shown that MVs can package bioactive molecules, nucleic acids (microRNAs (miRNAs) or mRNAs), and proteins that are reflective of the original cell type ( 6 , 7 ). Similarly, exosomes also contain massive and complex cargos of contents derived from parent cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been described that in different tumor models exist a correlation between tumor volumes and the concentration of circulating EVs in blood [ 47 ]. These EVs carry a cargo with precious information about the tumor, and they have become the substrate for biomarker digging in all types of malignancies [ 48 , 49 , 50 ] including prostate cancer [ 51 , 52 , 53 ].…”
Section: Extracellular Vesicles In Cancer Researchmentioning
confidence: 99%
“…In the last few years, several characterization and validation methods have been developed, for both research and clinical purposes, to analyze exosome purity and to quantify exosomal cargo. These methods include transmission electron microscopy (TEM), scanning electron microscopy (SEM), atomic force microscopy (AFM), nanoparticle tracking analysis (NTA), dynamic light scattering (DLS), resistive pulse sensing, enzyme-linked immunosorbent assay (ELISA), flow cytometry, fluorescence-activated cell sorting (FACS), and microfluidics and electrochemical biosensors [ 228 , 229 , 230 , 231 , 232 ]. The number of methods for quantifying exosomes has expanded as interest in exosomes has increased.…”
Section: The Potential Use Of Iace For Extracellular Vesicle Studimentioning
confidence: 99%